The Role of Artificial Intelligence Competencies and Organizational Support in Predicting Government Employee Performance: A Bibliometric and Systematic Review - Afzil Ramadian; Ismartaya; Revaliana Putri; Syakhira Fadla; Esih Nurasiah Zamil (Poltanesa, 2025)
This study focuses on AI competencies and organizational support in human resource management and information technology. It aims to help the government with policies for AI development and employee performance. Literature review analysis is the method used, collecting data from the Scopus database. Bibliometric and Dimension software helped analyze various indicators, like authors, articles, citations, institutions, and countries. The search found 53,672 documents from 2016 to 2025, including 27,057 chapters, 13,206 edited books, 6,175 articles, 5,029 monographs, 1,677 proceedings, and 528 preprints. With a focus on exploring AI skills and support in human resource management to help improve policies and employee performance. The study analyzes the impact of artificial intelligence on government employee performance, highlighting key authors and sources, emphasizing the importance of experience, and suggesting policy improvements for enhanced skills and competitiveness.